An Altered gp100 Peptide Ligand with Decreased Binding by TCR and CD8α Dissects T Cell Cytotoxicity from Production of Cytokines and Activation of NFAT - Schaft, Niels; Coccoris, miriam; Drexhage, Joost; Knoop, Christiaan; de Vries, Jolanda M.; Adema, Gosse J.; Debets, Reno (Frontiers in Immunology, 2013)
Altered peptide ligands (APLs) provide useful tools to study T cell activation and potentially direct immune responses to improve treatment of cancer patients. To better understand and exploit APLs, we studied the relationship between APLs and T cell function in more detail. Here, we tested a broad panel of gp100280–288 APLs with respect to T cell cytotoxicity, production of cytokines, and activation of Nuclear Factor of Activated T cells (NFAT) by human T cells gene-engineered with a gp100-HLA-A2-specific TCRαβ. We demonstrated that gp100-specific cytotoxicity, production of cytokines, and activation of NFAT were not affected by APLs with single amino acid substitutions, except for an APL with an amino acid substitution at position 3 (APL A3), which did not elicit any T cell response. A gp100 peptide with a double amino acid mutation (APL S4S6) elicited T cell cytotoxicity and production of IFNγ, and to a lesser extent TNFα, IL-4, and IL-5, but not production of IL-2 and IL-10, or activation of NFAT. Notably, T cell receptor (TCR)-mediated functions showed decreases in sensitivities for S4S6 versus gp100 wild-type (wt) peptide, which were minor for cytotoxicity but at least a 1000-fold more prominent for the production of cytokines. TCR-engineered T cells did not bind A3-HLA-A2, but did bind S4S6-HLA-A2 although to a lowered extent compared to wt peptide-HLA-A2. Moreover, S4S6-induced T cell function demonstrated an enhanced dependency on CD8α. Taken together, most gp100 APLs functioned as agonists, but A3 and S4S6 peptides acted as a null ligand and partial agonist, respectively. Our results further suggest that TCR-mediated cytotoxicity can be dissected from production of cytokines and activation of NFAT, and that the agonist potential of peptide mutants relates to the extent of binding by TCR and CD8α. These findings may facilitate the design of APLs to advance the study of T cell activation and their use for therapeutic applications.